New and rare micro-pagurid hermit crabs (Crustacea: Anomura: Paguridae) from the Caribbean Sea and Gulf of Mexico - Lemaitre, Rafael (Zootaxa, 2020)
Six species of hermit crabs of the family Paguridae from the Caribbean Sea and Gulf of Mexico region, including two new species, Anisopagurus asteriscus sp. nov. and Pagurus alarius sp. nov., are documented. The two new species are described, and recognition characters summarized for the four previously known species. Reports of the latter, Nematopaguroides fagei Forest & de Saint Laurent, 1968, N. karukera Lemaitre, Felder & Poupin, 2017, Paguriscus robustus Lemaitre, Felder & Poupin, 2017, and Pylopaguridium markhami McLaughlin & Lemaitre, 2001, represent range extensions for all four species. Color photographs are included for four of the species, as well as remarks on their taxonomy and distributions. All six species included can be categorized as micro-pagurids (with shield length rarely exceeding 2.0 mm), and were collected from cryptic reef habitats in Bocas del Toro, Panama; the French Antillean island of Guadeloupe; and the Gulf of Mexico coasts of Louisiana, Yucatán, and Florida Keys. The discovery of these new or rare species supports the conclusion of recent studies that the diversity of pagurids from the Caribbean region has yet to be fully realized.